The Relationship between Pregnancy Exercise in Primigravida and The Prolonged Second Stage of Labor - wiwit marliana; Hikmah Hikmah (Jurnal Publikasi Kesehatan Masyarakat Indonesia, 2022)
Prolonged second stage of labor is one of the mortality causes in women, due to its risk of infection, decrease in energy, dehydration, and postpartum hemorrhage. The duration of labor is determined by three factors: power (the ability of the mother to push the baby from the womb), passage (the condition of the birth canal), and passenger (the condition of the fetus). The only controllable factor is power. The mother’s ability to push and expulse the fetus can be augmented by pregnancy exercises. This study is aimed to determine the effect of pregnancy exercises in primigravidas with the prevalence of prolonged second stage of labor in PKU Muhammadiyah Gamping Hospital in Yogyakarta. This study is an observational study with a cross-sectional design. A total of 57 samples were obtained through purposive sampling, all of whom are patients giving birth at PKU Muhammadiyah Gamping Hospital in Yogyakarta. Data analysis was done with univariate and bivariate chi-square. 31 samples (54,3%) attended pregnancy exercise classes, and 4 (7,0%) had a prolonged second stage of labor. A total of 26 samples (45,6%) did not practice any pregnancy exercises, and 22 of them (38,5%) had a prolonged second stage of labor. Mothers who did not practice any pregnancy exercises had a 6,558 higher risk of the prolonged second stage of labor compared to those who had practiced pregnancy exercises (p =0,000, 95% CI 2,590-16,606). There was a significant correlation between pregnancy exercises with the prevalence  of prolonged second stage labor in PKU Muhammadiyah Gamping Hospital in Yogyakarta.